The complete chloroplast genome of Schrenkiella parvula (Brassicaceae). (2nd September 2016) - He, Qi; Hao, Guoqian; Wang, Xiaojuan; Bi, Hao; Li, Yuanshuo; Guo, Xinyi; Ma, Tao
Abstract: Schrenkiella parvula is an Arabidopsis-related model species used here for studying plant stress tolerance. In this study, the complete chloroplast genome sequence of S. parvula has been reported for the first time. The total length of the chloroplast genome was 153 979 bp, which had a typical quadripartite structure. The annotated plastid genome includes 87 protein-coding genes, 39 tRNA genes and 8 ribosomal RNA genes. The evolutionary relationships revealed by our phylogenetic analysis indicated that S. parvula is closer to the Brassiceae species when compared with Eutrema salsugineum.